ASRAMA MAHASISWA WASAKA II UNIVERSITAS LAMBUNG MANGKURAT BANJARBARU - Ilhami, Indra; Tharziansyah, Muhammad (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Wasaka II is one of the dormitories owned by university of lambung mangkurat. The interest of students, especially students who have just entered the lecture study period every year, has increased interest in living in dormitories, this is due to cheap housing costs and dormitory positions that are still in the campus area. The background of designing the Wasaka II Student Dormitory is how to design a dormitory that is comfortable for its residents and fulfilled its capacity to accommodate. The concept of approaching green architecture was chosen because it can increase comfort, this is in line with the function of the dormitory as a residence that is expected to give a comfortable impression to its residents.The dormitory certainly cannot be separated from the uniformity of the existing ULM building area, for that the Geometries of Connection method was chosen; namely as a connecting building / environment that will be designed with geometric patterns in this case such as buildings or access that already exist around the site, thus allowing the design of a new